To Evaluate Urinary Incontinence in Female Athletes & Its Association with Disordered Eating in Elite Female Athletes - Amrit Kaur (International Journal of Allied Medical Sciences and Clinical Research, 2020)
The purpose of this study was to evaluate the association between urinary incontinence and disordered eating, in elite female athletes. A cross-sectional study was done including 100 young and healthy women: 50 elite athletes aged 24.54 ± 3.05 years and 50 non-athletes aged 20.84 ± 2.02 years. The International Consultation on Incontinence Questionnaire-Urinary Incontinence-Short Form was used to screen urinary incontinence. The Eating Attitude Test-26 Questionnaire was used to screen disordered eating. Data was analyzed using Odds ratios with 95% confidence intervals (95% CI) to estimate the association between UI and disordered eating. Statistical analysis revealed that Prevalence of urinary incontinence in elite athletes and non- athletes was 29.6% and 14.4%; P < 0.001 respectively. Prevalence of eating disorder in elite athletes and non- athletes was 13.5% and 4.6%; P < 0.001 respectively. Urinary incontinence was associated with disordered eating only in the athletes. After adjustment for age, type of sport, Sports practice frequency (hours/week), athletes with disordered eating presented increased odds of urinary incontinence of any type over non-athletes (OR = 9.23; 95% CI: 0.93-90.8). The study concludes that athletes with disordered eating were three times more likely to present urinary incontinence than women without disordered eating.